Patients parameters and results of the tilt table test depending on referrals. (3rd October 2022) - Kirnosova, K; Keller, H; Stoellberger, C
Abstract: Introduction: The tilt table examination (TTT) is used to investigate patients with syncope for 50 years, and was downgraded by the 2018 Guidelines of the European Society of Cardiology for syncope-evaluation from class I to II a/b. Aim: Aim of the study was to assess changes in the referrals for TTT from 2014 to 2018. In addition, it was examined if there were differences in the history, clinical findings, and results of the TTT among patients depending on the referral for TTT. Patients and methods: Included in the retrospective cohort study were 205 patients, 49% females, mean age 52 (15–82) years, in whom TTT was carried out between 2014 and 2018 in a cardiology department. Information from the discharge letters and electronic hospital information system was collected. Results: Referrals for TTT were suspected orthostatic hypotension (OH) (n=53), suspected reflex syncope (n=98), and unexplained syncope (n=54). By TTT the diagnosis of OH was established in 32%, reflex syncope in 27%, and postural orthostatic tachycardia syndrome in 16%. There was an increase of positive TTT findings from 2016 to 2018 (54 to 79%, p=0.039). The referrals for unexplained syncope decreased from 2014 to 2018 (33 vs. 14%, p=0.039). Compared to patients with suspected reflex syncope, patients with unexplained syncope suffered more from coronary artery disease (CHD) (19 vs. 5%, p=0.011) and arrhythmias (24 vs. 10%, p=0.032), were more often taking beta-blockers (26 vs. 7%, p=0.002) and more often had ST-segment abnormalities (11 vs. 1%, p=0.008). Compared to patients with suspected OH, patients with unexplained syncope suffered more from palpitations (11 vs. 8%, p=0.0024). Compared to patients with suspected reflex syncope, patients with suspected OH had more comorbidities such as CHD (17 vs. 5%, p=0.036), hypertension (45 vs. 18%, p=0.01), diabetes mellitus (25 vs. 3%, p=0.0) and synucleinopathies (6 vs. 0%, p=0.042) and took more antidiabetic (23 vs. 4%, p=0.001), antithrombotic (42 vs. 12%, p=0.0), diuretic (15 vs. 2%, p=0.004), beta blocking (23 vs. 7%, p=0.009), anticonvulsant (6 vs. 0%, p=0.042), antiparkinsonian (6 vs. 0%, p=0.042), antidepressant agents (26 vs. 11%, p=0.022) and statins (26 vs. 8%, p=0.004). Compared to patients with suspected OH, patients with suspected reflex syncope suffered more from prodromes like flushing (17 vs. 2%, p=0.001) and nausea (33 vs. 8%, p=0.004). Conclusions: If patients are referred for appropriate reasons, the TTT has a high diagnostic value. The results confirm other studies indicating that unexplained syncope may suggest a cardiac origin. Funding Acknowledgement: Type of funding sources: None.